PENERAPAN PROGRAM JUMAJI DALAM PENGUATAN DIMENSI BERIMAN DAN BERTAKWA DI SDN KRAGILAN 01 - Annisaa Nur Aini; Dwi Anggraeni Siwi; Koko Prasetyo (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Faith and piety education at SD Negeri Kragilan 01 is not supported by extracurricular activities or additional hours at school. The independent curriculum in improving the religious character of students then holds a JUMAJI program in strengthening the profile of Pancasila students in the dimensions of faith and piety. The purpose of this study is to describe the application and constraints of the Jumaji program in strengthening the profile of Pancasila students in the dimensions of faith and piety at Kragilan 01 State Elementary School. This type of research is qualitative research. This research method uses descriptive qualitative methods. The results of the study can be concluded that, 1) Jumaji activities include reading the Qur'an, memorizing short letters, listening to lectures/motivational teachers and giving alms. The program has fulfilled the aspects of the Pancasila student profile of the dimensions of faith and piety, namely religious morals, personal morals, morals to nature, morals to fellow human beings, morals to the state. 2) The obstacles to the implementation of the Jumaji program include; Lack of time consistency in implementation, different reading abilities of students, lack of infrastructure facilities, the surrounding environment, namely limited space and the influence of friends.